2013
DOI: 10.11646/zootaxa.3641.4.3
|View full text |Cite
|
Sign up to set email alerts
|

A new species of <i>Ceratophysella</i> (Collembola: Hypogastruridae) from Japan, with notes on its DNA barcode and a key to Japanese species in the genus

Abstract: Ceratophysella comosa sp. nov. was collected from ascomata of Ciborinia camelliae in Japan and the morphological and molecular characteristics of the species are described here. The species has 3 + 3 cephalic spines as in Ceratophysella loricata and Ceratophysella pilosa, but a plurichaetosis intermediate between C. loricata (absent) and C. pilosa (strong). The new species can be distinguished from these two species also by the number of setae on the first thorax segment and ventral tube. Partial DNA sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Moreover, these values are in line with the usual 'barcoding gap' described so far in the family Hypogastruridae (e.g. Nakamori 2013;Skarżyński et al 2018) but also more generally in Collembola (e.g. Porco et al 2014;Nilsai et al 2017).…”
Section: Dna Barcodingsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, these values are in line with the usual 'barcoding gap' described so far in the family Hypogastruridae (e.g. Nakamori 2013;Skarżyński et al 2018) but also more generally in Collembola (e.g. Porco et al 2014;Nilsai et al 2017).…”
Section: Dna Barcodingsupporting
confidence: 88%
“…Traditionally, the most commonly used method in the taxonomy of the genus Ceratophysella, as in other Collembola, is the analysis of morphological features (Gisin 1949;Stach 1949;Cassagnau 1959;Yosii 1960;Bourgeois and Cassagnau 1972;Babenko et al 1994;Jordana et al 1997;Christiansen and Bellinger 1998;Fjellberg 1998;Thibaud et al 2004). Recently, hybridization in laboratory conditions and DNA barcoding have also been used, although on a small scale (Skarżyński 2004a(Skarżyński , b, c, 2005Porco et al 2012;Nakamori 2013). Research on the Xenylla maritima complex (Skarżyński et al 2018) and Ceratophysella comosa Nakamori, 2013 showed that combined use of the morphological and genetic criteria may bring good results in establishing species status and support in the family Hypogastruridae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR primers and conditions used for construction of the reference database are listed in Table S1 2 . When a sample was not amplifiable with an ordinary primer pair (Folmer et al 1994) and the degenerate primers for Collembola (Nakamori 2013), amplification using other combinations of several available primers were tried so that the sequence of the gene region that was targeted in metabarcoding (to be described later) was obtained. We also sequenced the targeted gene regions from single specimens by multiplexing in a sequencing run of a 454 GS Junior sequencer (Roche, Basel, Switzerland) using a method (H. Aoyama et al unpublished) analogous to that of Shokralla et al (2014); the former method used ligation in library preparation to add adapters for 454 technology to amplified gene fragments, whereas the latter utilized fusion primers for the purpose.…”
Section: Collection Of Reference Sequencesmentioning
confidence: 99%